Physical and mental health of informal caregivers before and during the COVID-19 pandemic in the United States - Emery L Ngamasana; Meagan Zarwell; Laura H Gunn (BMC, 2023)
Abstract Background Informal caregiving, a common form of social support, can be a chronic stressor with health consequences for caregivers. It is unclear how varying restrictions during the COVID-19 pandemic affected caregivers' physical and mental health. This study explores pre-post March 2020 differences in reported days of poor physical and mental health among informal caregivers. Methods Data from the 2019/2020 Behavioral Risk Factor Surveillance System survey were used to match, via propensity scores, informal caregivers who provided care during COVID-19 restrictions to those who provided care before the pandemic. Negative binomial weighted regression models estimated incidence rate ratios (IRRs) and differences by demographics of reporting days of poor physical and mental health. A sensitivity analysis including multiple imputation was also performed. Results The sample included 9,240 informal caregivers, of whom 861 provided care during the COVID-19 pandemic. The incidence rate for days of poor physical health was 26% lower (p = 0.001) for those who provided care during the COVID-19 pandemic, though the incidence rates for days of poor mental health were not statistically different between groups. Informal caregivers with low educational attainment experienced significantly higher IRRs for days of poor physical and mental health. Younger informal caregivers had a significantly lower IRR for days of poor physical health, but higher IRR for days of poor mental health. Conclusions This study contends that the physical and mental health burden associated with informal caregiving in a period of great uncertainty may be heightened among certain populations. Policymakers should consider expanding access to resources through institutional mechanisms for informal caregivers, who may be likely to incur a higher physical and mental health burden during public health emergencies, especially those identified as higher risk.